Risk Analysis of SIP Monitoring and Control System User Interface - Markevičius, V.; Navikas, D.; Jonynas, V.; Dubauskienė, N. (Elektronika ir Elektrotechnika, 2008)
There are analyzed properties of syringe infusion pumps (SIP) control system user interface that allows reducing patient risk during the infusion. Also there are analysed main reasons of SIP security problems for the patient. Patient risk variation evaluation method according to statistical SIP reliability and personel human mistake factor during the work is presented. Infusion for one patient using n single syringe infusion pumps reliability and infusion for one patient using SIPCS with n syringe infusion pumps reliability calculation example results are shown. Ill. 6, bibl. 3 (in English; summaries in English, Russian and Lithuanian).